Small-molecule allosteric activator of ubiquitin-specific protease 7 (USP7) - Isabella Jaen Maisonet; Mona Sharafi; Emilie J. Korchak; Andres Salazar-Chaparro; Ariana S. Bratt; Tvesha Parikh; Anthony C. Varca; Binita Shah; Michael Darnowski; Mia Chung; Wei Pin Teh; Jianwei Che; et al. (Proceedings of the National Academy of Sciences, 2025)
Ubiquitin-specific protease 7 (USP7) is a deubiquitylase essential for cell homeostasis, DNA repair, and regulation of both tumor suppressors and oncogenes. Recently, haploinsufficiency of USP7 has been associated with Hao–Fountain syndrome (HAFOUS), a rare neurodevelopmental disorder. Although a range of USP7 inhibitors have been developed over the last decade, in the context of HAFOUS, USP7 activators may represent a more relevant approach. To address this challenge, we report the identification and characterization of a small-molecule activator of USP7 called MS-8. Structural and functional studies show that MS-8 allosterically activates USP7, mimicking the endogenous autoactivation mechanism of the enzyme. We observed that MS-8 engages and activates mutant USP7 in a cellular context, impacting downstream proteins. Taken together, our study provides validation of the USP7 activator that paves the way toward activation-driven USP7 pharmacology.